Analysis of ambient air quality using fuzzy air quality index: a case study of Delhi, India. (2015) - Mishra, Dhirendra; Goyal, Pramila
Ambient air quality is one of the most serious environmental concerns in urban areas around the world, especially in developing countries. In recent years, there has been increasing concern over the adverse effects of air pollution on human health. In the present study, the concentrations of air pollutants and their adverse effect at various locations over Delhi are studied using fuzzy air quality index (FAQI). The 24-hourly average concentrations of main criteria pollutants viz., fine particulate matter (PM2.5 ), nitrogen dioxide (NO2 ), carbon monoxide (CO) and ozone (O3 ) over the years 2008 to 2012 have been used for the analysis at three different locations in Delhi (residential-Sirifort, industrial-DCE and busiest traffic intersection-ITO junction). Further, the weightages of criteria pollutants have been determined using an analytical hierarchical process to access the air quality index. The developed methodologies also have been compared with the conventional approach and validated with different statistical measures. The results clearly indicate that the air quality of Delhi is degraded and lies in the ranges of 'bad' and 'very bad' categories.